Contribution of Fireworks to Environmental Pollution: Exploring the Impact of Fireworks on Environmental and Human Well-being (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This article analyzed the contribution  of fireworks to environment pollution.Fireworkscan unleash a shower of toxins into soil and water, and scientists are onlybeginning to figure out what that means for human health.It also analyzedifferent types of fireworks containing different types of harmful substancesfor air,soil,water and humans.Fireworks contains Perchlorates, particulates and metallic compounds.